Impact of internal heat gains on building’s energy performance - Lapinskienė, Vilūnė; Motuzienė, Violeta; Džiugaitė-Tumėnienė, Rasa; Mikučionienė, Rūta (International Conference “Environmental Engineering”, 2017)
Internal heat gains from occupants, equipment and lighting contribute a significant proportion of the heat gains in an office space. Usage of ICT in offices is growing; on the other hand, their efficiency is also improving all the time. Increasing energy efficiency in buildings have led to the situation, when new, well insulated office buildings, with high internal gains within the working hours may cover low heating energy demand. Such buildings, even in heating dominated countries, such as Lithuania, often also suffer from overheating during the winter heating season. The paper presents the analysis of energy demand of the office building for various plug loads (ICT equipment) internal gains scenarios and demonstrates its influence on buildings energy performance. Simulation results enable to conclude, that when assessing sustainability and energy bills of the building, plug loads play a very important role. Meanwhile, assessing just energy performance influence is very small. Energy performance certification results show, that plug loads may influence energy performance label just for buildings corresponding A+ and A++ labels).
Keywords: office; energy performance; internal gains; simulation; certification